2012
DOI: 10.1242/dev.084871
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial deletion of murine Jag1 leads to valve calcification and congenital heart defects associated with Alagille syndrome

Abstract: The Notch signaling pathway is an important contributor to the development and homeostasis of the cardiovascular system. Not surprisingly, mutations in Notch receptors and ligands have been linked to a variety of hereditary diseases that impact both the heart and the vasculature. In particular, mutations in the gene encoding the human Notch ligand jagged 1 result in a multisystem autosomal dominant disorder called Alagille syndrome, which includes tetralogy of Fallot among its more severe cardiac pathologies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
86
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(94 citation statements)
references
References 68 publications
6
86
0
2
Order By: Relevance
“…4C,e-f). While Jag1 null embryos show partial but significant EndMT defect (Hofmann et al, 2012;Wang et al, 2013), Jag1 protein expression (Fig. 4C,g-h) and Jag1 mRNA expression (data not shown) in AVC endocardial cells were below the detection limit.…”
Section: Endmt Defect Of Tmem100 Null Avc Explants In Ex Vivo Culturementioning
confidence: 80%
See 2 more Smart Citations
“…4C,e-f). While Jag1 null embryos show partial but significant EndMT defect (Hofmann et al, 2012;Wang et al, 2013), Jag1 protein expression (Fig. 4C,g-h) and Jag1 mRNA expression (data not shown) in AVC endocardial cells were below the detection limit.…”
Section: Endmt Defect Of Tmem100 Null Avc Explants In Ex Vivo Culturementioning
confidence: 80%
“…While Notch signaling is also required for normal endocardial cushion development (Timmerman et al, 2004;Hofmann et al, 2012;Wang et al, 2013), the expression patterns of Notch1 and NICD, an activated form of Notch receptor, in AVC endocardial cells were comparable between wild-type and Tmem100 null embryos (Fig. 4C,a-d).…”
Section: Endmt Defect Of Tmem100 Null Avc Explants In Ex Vivo Culturementioning
confidence: 94%
See 1 more Smart Citation
“…Further in vivo evidence of this inhibitory role has been demonstrated in mice heterozygous for Notch1, Rbpj, Jagged1 and Hey2, which develop aortic valve calcification. [67][68][69] Those studies demonstrated that valve development genes may potentially play a role in this adult-onset disease and the mechanisms by which loss of Notch signaling leads to calcification are being investigated. 70 Sox9, which encodes an SRY-related transcription factor found to play a role in acquired VHD.…”
Section: Calcific Valve Diseasementioning
confidence: 99%
“…In diseased valves, the VEC monolayer is disrupted in association with abnormal changes in ECM organization and altered biomechanics 4,5 . In addition, studies in mouse models suggest that VEC dysfunction is the underlying cause of valve disease 1,[6][7][8][9] . As VECs play an important role in valve development, maintenance, and disease, it is important that we fully define their temporal phenotypes in order to advance the field and understand mechanisms of disease.…”
Section: Introductionmentioning
confidence: 99%